Aesthetics in Arabic thought : from pre-Islamic Arabia through al-Andalus - Puerta Vílchez, José Miguel. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2017)
In Aesthetics in Arabic Thought from Pre-Islamic Arabia through al-Andalus José Miguel Puerta Vílchez analyzes the discourses about beauty, the arts, and sense perception that arose within classical Arab culture from pre-Islamic poetry and the Quran (sixth-seventh centuries CE) to the Alhambra palace in Granada (fourteenth century CE). He focuses on the contributions of such great thinkers as Ibn Ḥazm, Avempace, Ibn Ṭufayl, Averroes, Ibn ʿArabī, and Ibn Khaldūn in al-Andalus, and the Brethren of Purity, al-Tawḥīdī, al-Fārābī, Avicenna, Alhazen, and al-Ghazālī in the East. The work also explores literary criticism, calligraphy, music, belles-lettres ( adab ), and erotic literature, and highlights the contribution of Arab humanism to shaping the field of Aesthetics in the West.